Latihan Peningkatan Kebugaran Jasmani Pemain Bola Voli Putra dan Putri SMPN 2 Bajawa melalui Pendampingan Kegiatan Ekstrakurikuler Sekolah - Wiru, Mikael Leonardo Soko; Vinsensius Dae; Joanne Batistan Lako Yti; Sanecty Mardelon Wasa Weto; Yohanes Bayo Ola Tapo (Mutiara Pendidikan dan Olahraga, 2026)
This community-based mentoring study aims to improve the physical fitness of male and female volleyball players at SMPN 2 Bajawa through structured extracurricular mentoring activities. Physical fitness is a crucial aspect in supporting athletes' performance, especially in volleyball, which requires strength, agility, endurance, and coordination. This study employed a descriptive qualitative approach, with data collected through observation, interviews, and documentation of the volleyball extracurricular program. The mentoring method applied a structured training approach that includes both general and specific physical exercises, such as muscle strength training, agility drills, and cardiorespiratory endurance exercises, carried out routinely for eight weeks under the direct guidance of coaches and physical education teachers. The results showed a significant improvement in the physical fitness of participating students, indicated by better fitness test scores and improved game performance. In addition, the mentoring activities positively influenced students' interest, motivation, and discipline in participating in extracurricular activities. This activity demonstrates that structured mentoring in extracurricular volleyball programs can be an effective strategy to develop students’ overall physical fitness while also supporting character development and sporting achievement within the school environment.